THE ROLE OF INNATE IMMUNITY FACTORS IN TUMORIGENESIS PROCESS - O. A. Svitich; A. B. Filina; N. V. Davydova; L. V. Gankovskaya; V. V. Zverev (Медицинская иммунология)
The theory of polyetiological tumorigenesis is one of the most important theories of carcinogenesis. A great place in this theory is given to the role of inflammatory component, which is implemented via the factors of innate immunity. I.e., toll-like receptors (TLRs), chemokines and their receptors are related to innate immunity. Activation of TLRs may lead to regress or progression of cancer process. It is known that TLR3, TLR5, TLR7, TLR9 have the greatest anti-tumor effect due to the dendritic cells (DCs)-mediated activation of type I T helpers, activation of M1-type macrophages and Treg inhibition. Stimulation of TLR2 and TLR4 exerts an activating effect upon the tumor, by the MyD88 hyperactivation and secretion of IL-6 and TNFα, but exact mechanisms are not fully understood. In addition to TLRs, chemokines and their receptors have a great influence on the cancer development. It is shown that CCL2, CCL4, CCL17, CCL22 and CXCL12, which are secreted by cancer microenviroment, activate chemotaxis of tumor cells. It is also known that the chemokines activate CXCR4 and CCR7 (expressed by tumor cells) thus leading to metastasis.It is shown that there is an association between some gene polymorphisms of TLRs’, chemokines and their receptors, and development of cancer.Thus, we may conclude that the role of TLRs and chemokines is important in oncogenesis. Further study of innate immunity factors influencing tumorigenesis are important for finding new approaches to cancer therapy and new potential vaccines against cancer.